Parental Child Rearing Practices in Palestine: A Cross-Sectional Study - Maha Atout RN, PhD; Intima Alrimawi RN, PhD; Mutaz Dreidi RN, PhD; Ahmad Rajeh Saifan RN, PhD; Eman Abusalameh RN, MSN; Nabeel Al-Yateem RN, PhD (SAGE Publishing, 2021)
The objectives of this study were to explore parenting practices from the perspectives of Palestinian parents and their children, and concordance between parents and children in their reports of parenting practices, in a culture that is underrepresented in the literature. A descriptive cross-sectional design was used. The Alabama Parenting Questionnaire (APQ) was administered to 120 parents and 120 children drawn from 4 districts in Palestine. Children had higher scores on parental involvement, positive parenting, poor monitoring, inconsistent discipline, and corporal punishment. Three significant parent-child relationships were obtained1: parental involvement ( r  = .276, P  = .003), positive parenting ( r  = .0301, P  = .001), and poor parental monitoring ( r  = −.241, P  = .008). The findings of this study might be used by Palestinian authorities and policy-makers to formulate guidelines and training to aid parental decision-making about child rearing.